Effects of amino-modified biofilm carriers on biogas production in the anaerobic digestion of corn straw. Issue 21 (18th September 2020) - Liu, Yongdi; Lin, Chaoba; Jia, Honghua; Yong, Xiaoyu; Xie, Xinxin; Wu, Xiayuan; Zhou, Jun; Wei, Ping
ABSTRACT: This paper studied the property of three different biofilm carriers added into the anaerobic digestion systems, a granular activated carbon, a polyacrylonitrile, and a polyacrylonitrile modified with diethylenetriamine (PAN-NH2 ). The PAN-NH2 system kept the maximum biogas and methane production, which were 42.69% and 37.29% higher than the control system, respectively. The value of pH and chemical oxygen demand, the content of total solid and volatile solid, volatile fatty acids concentration, coenzyme F420 concentration, and microbial community analysis were investigated during the anaerobic digestion process. The PAN-NH2 system had the highest removal efficiency of the pollutants and regulated the pH of the system better than other systems. The result of high-throughput sequencing analysis showed that the addition of biofilm carriers and mediation with amino-groups adjusted system pH and improved biogas and CH4 production by reducing the relative abundance of bacteria in the hydrolysis/acidogenesis stages. Methanosarcina gradually replaced other methanogens during the experimental runs and was the dominant methanogen at the end of the anaerobic digestion process. GRAPHICAL ABSTRACT: